The relationship between Family Duties in Elderly Caring with Independence Level of Elderly in activity daily living at Sumolawang Hamlet Sumolawang Village Mojokerto Regency - heri triwibowo; Heni Frilasari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
The family has a very important duty in elder care. In the process of getting older, a person experiences a physical, mental and social setback little by little until he cannot perform his daily tasks again. Therefore, the implementation of family duties must be optimized so that the elderly can live independently and productively in the conditions. The purpose of this study is to analyze the relationship between family duties in caring for elderly with the level of independence of elderly in everyday life activities in Sumolawang hamlet Sumolawang village, Mojokerto regency. In this study, the population is family and elderly in Sumolawang hamlet Sumolawang village, Mojokerto regency and the sample is family and elderly who have fulfilled inclusion criteria amounting to 35 people. The sample selection was done by a nonprobability sampling of purposive sampling type and in collecting data was used instrument questionnaire sheet for family duty in caring for elderly and Katz index observation sheet for the level of independence of elderly in daily life activity. The result of data analysis using SPSS chi-square test (c2) obtained value (0,607)> a (0,05), which means there is no relation between family duty in caring elderly with the level of independence of elderly in daily life activity in Sumolawang hamlet Sumolawang village, Mojokerto regency. This is due to a different understanding of the elderly in accepting the implementation of maintenance tasks of his family. Efforts to prevent the occurrence of dependence on the elderly can be done by improving the implementation of family duties in caring for the elderly. Keywords: Family Duties, Degree of Independence Elderly The family has a very important duty in elder care. In the process of getting older, a person experiences a physical, mental and social setback little by little until he cannot perform his daily tasks again. Therefore, the implementation of family duties must be optimized so that the elderly can live independently and productively in the conditions. The purpose of this study is to analyze the relationship between family duties in caring for elderly with the level of independence of elderly in everyday life activities in Sumolawang hamlet Sumolawang village, Mojokerto regency. In this study, the population is family and elderly in Sumolawang hamlet Sumolawang village, Mojokerto regency and the sample is family and elderly who have fulfilled inclusion criteria amounting to 35 people. The sample selection was done by a nonprobability sampling of purposive sampling type and in collecting data was used instrument questionnaire sheet for family duty in caring for elderly and Katz index observation sheet for the level of independence of elderly in daily life activity. The result of data analysis using SPSS chi-square test (c2) obtained value (0,607)> a (0,05), which means there is no relation between family duty in caring elderly with the level of independence of elderly in daily life activity in Sumolawang hamlet Sumolawang village, Mojokerto regency. This is due to a different understanding of the elderly in accepting the implementation of maintenance tasks of his family. Efforts to prevent the occurrence of dependence on the elderly can be done by improving the implementation of family duties in caring for the elderly.